Drilling Capability of Orthodontic Miniscrews: In Vitro Study - Alessandra Marchi; Matteo Camporesi; Maurizio Festa; Luis Salvatierra; Sara Izadi; Giampietro Farronato (Dentistry Journal, 2020)
The aims of this study were to assess the values and mechanical properties of insertion torque (IT) of steel miniscrews inserted in artificial bone blocks (Sawbones, Pacific Research Laboratories, Vashon, WA, USA) with different bone densities and to detect any scratches on the surface of the miniscrews after insertion. Forty self-drilling miniscrews (Leone S.p.A. ø 1.75 mm, L 8 mm) have been inserted into bone blocks that mimic different stability conditions (density: 20 PCF—pounds per cubic foot, 40 PCF, and 30 + 50 PCF with 2 mm and 4 mm of cortical bone). Before insertion and after removal, all miniscrews were inspected with a stereomicroscope 5x and a SEM to detect potential microscopic cracks. Using an electronic surgical motor (W&H Dentalwerk Bürmoos GmbH, Werner Bader Str. 1, 5111 Bürmoos, Austria), the maximum insertion torque value was registered. Stereomicroscope and SEM examination did not indicate any morphological and surface structural changes to the miniscrews, irrespective of the bone density they were inserted into. The findings showed that IT increased significantly with increasing bone density. In each artificial bone block, morphostructural analysis demonstrated the adequate mechanical properties of the self-drilling miniscrews. IT measurements indicated torque values between 6 and 10 Ncm for blocks with a density of 30 + 50 PCF, whereas the suggested values are between 5 and 10 Ncm.